(untitled) - United Nations; Department of Economic and Social Affairs (New York, 1970)
For the purpose of this report, the tern "mineral resources", meaning natural mineral concentrations capable of exploitation, will embrace both mineable products, notaby metallic minerals, minerals used in the chemical and quarried products such as cement and construction materials, clays, sands and gravels.
Keywords: Mỏ và tài nguyên khoáng sản,Mines and mineral resources; Phát triển quốc gia,Developing countries